2006
DOI: 10.1071/fp06078
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal aperture can compensate altered stomatal density in Arabidopsis thaliana at growth light conditions

Abstract: Stomatal density of transgenic Arabidopsis thaliana plants over-expressing the SDD1 (stomatal density and distribution) gene was reduced to 40% and in the sdd1-1 mutant increased to 300% of the wild type. CO2 assimilation rate and stomatal conductance of over-expressers and the sdd1-1 mutant were unchanged compared with wild types when measured under the light conditions the plants were exposed to during growth. Lower stomatal density was compensated for by increased stomatal aperture and conversely, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 28 publications
4
73
2
Order By: Relevance
“…These findings indicated that increased stomatal aperture compensated for the lower stomatal density in the SDD1 plants while reduced aperture in the sdd1-1 plants offset the greater number of stomata. However, at high light intensities, low g s in the SDD1 overexpressors and restricted CO 2 diffusion limited A to 80% of the wild type (Büssis et al, 2006). These findings exemplify the role of both the physical and functional stomatal features in determining g s and that manipulation of physical attributes may be counterbalanced by modifications in function.…”
Section: Stomatal Densitymentioning
confidence: 63%
See 3 more Smart Citations
“…These findings indicated that increased stomatal aperture compensated for the lower stomatal density in the SDD1 plants while reduced aperture in the sdd1-1 plants offset the greater number of stomata. However, at high light intensities, low g s in the SDD1 overexpressors and restricted CO 2 diffusion limited A to 80% of the wild type (Büssis et al, 2006). These findings exemplify the role of both the physical and functional stomatal features in determining g s and that manipulation of physical attributes may be counterbalanced by modifications in function.…”
Section: Stomatal Densitymentioning
confidence: 63%
“…Transgenic plants overexpressing SDD1 have a 40% reduction in stomatal densities compared with the wild type (Von Groll et al, 2002). In a comparative study, Büssis et al (2006) showed no difference in g s or assimilation rate when measured under growth photosynthetically active photon flux density (PPFD) conditions (180 mmol m 22 s 21 ) between the overexpressing SDD1 plants, the sdd1-1 mutants, and wild-type controls. These findings indicated that increased stomatal aperture compensated for the lower stomatal density in the SDD1 plants while reduced aperture in the sdd1-1 plants offset the greater number of stomata.…”
Section: Stomatal Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…7). Studies with stomatal density and distribution (sdd1-1) mutants in Arabidopsis also showed that stomatal density cannot be correlated directly with g s , because increased numbers can be compensated for by decreased functional stomatal aperture (Büssis et al, 2006;Lawson and Blatt, 2014). This compensation mechanism appears to be environmentally dependent, in that no difference in g s or assimilation rates were detected when the wild type, sdd-1 mutants with increased stomatal density, and SDD1 overexpression lines with a 40% reduction in stomatal number were compared under light conditions of 180 mmol m 22 s 21 PPFD (Berger and Altmann, 2000;Von Groll et al, 2002).…”
Section: Discussionmentioning
confidence: 99%